Legal Analysis of Money Laundering Crimes from the Perspective of Transnational Organized Crime - Saputri, Fitri Arianti (Ipso Jure, 2026)
The development of globalization has led to an increase in money laundering as part of transnational organized crime, which has serious impacts on economic stability and national legal systems. This study aims to analyze the legal provisions of money laundering within the national and international legal frameworks, and to examine the ambiguity of the norm regarding "proceeds of crime" and its implications for evidence. The research method used is normative legal research with a statutory and conceptual approach, supported by primary, secondary, and tertiary legal materials through literature studies, and analyzed qualitatively using legal interpretation methods. The results show that although legal regulations have accommodated international principles, there is still ambiguity in the norm regarding the definition of "proceeds of crime," which gives rise to multiple interpretations and legal uncertainty. This impacts on the difficulty of proving, particularly in linking assets to predicate crimes in a cross-border context. Furthermore, limited international cooperation and differences in legal systems further complicate law enforcement. Therefore, normative reconstruction is needed through a more assertive and restrictive formulation and strengthening of the asset-based approach to increase the effectiveness of money laundering eradication.